“A Study on Manipulation of Anxiety of The Employees in The It Industry w.r.t. MIDC, PMC” (International Journal of Food and Nutritional Sciences, 2022)
According to Freud, anxiety is a feeling of impending danger that can be based on objective, neurotic, or moral threats. Anxiety is a feeling of impending danger. Sigmund Freud (1856-1939) considered three types. Objective anxiety results from a real threat in the physical world to one's well-being, as when a ferocious-looking dog appears from around the corner. The other two types are derived from objective anxiety. Neurotic anxiety results from the ego feeling overwhelmed by the id, which threatens to express its irrationality in thoughts and behavior. There is a fear of external punishment for such expression. Moral anxiety is based on a feeling that one's internalized values are about to be compromised. There is a fear of self-punishment (e.g., guilt) for acting contrary to one's values. Operating at the unconscious level, it employs defense mechanisms to distort or deny reality.